DEVELOPMENT OF TRANSPORT AND COMMUNICATION SYSTEM IN GOALPARA DURING COLONIAL PERIOD -AN ANALYSIS - Boroowa, Diganta Kumar (International Journal of Research -GRANTHAALAYAH, 2020)
This paper tries to study the development of modern transportation systems in the Goalpara. Assam being the gateway to the other states of the North Eastern Region of the country, the need for development of transport and communication in the state is of vital importance for speedy economic development of the region. Due to its geographical location, transport has been a major bottleneck in the process of economic progress of the state. The transport and communication is a part and parcel for the economic development of a state. The transport system made the dealings very close between producers and consumers. Every old account of Assam suggested that most of the travelers used horses, ponies, elephants, bullock cart, palanquins and country-boats as a means of transportation and communication. The existing infrastructure and facilities of transport are not adequate to meet the requirements. To meet the demands of the new modes of resource extraction, the British colonial rulers developed transportation system in Goalpara. Goalpara was a gateway of the eastern countries as well as transit point of Bengal and Assam. In early, only river courses became the means of communication for trade activities. The trade facilities of Goalpara district compelled the colonial administrator to build up good transport system. Government of British India constructed roads, railways line, tram line and provided steam service on the river for the purpose of trade activities in the district.